(untitled) (Journal of the College of Basic Education, 2023)
Metacognitive strategies are a style of teaching that allows the learner to use his or her own skills to develop independent learning that enables them to take self-responsibility for learning. And that it is a set of procedures that the student undertakes under the supervision and guidance of the teacher to be aware and aware of his thinking processes and management. The educated and the teacher together. The study aimed to identify the effect of using the graphic shapes strategy in learning some basic football skills and to identify the preference between the graphic shapes strategy and the tired style in learning some basic football skills. As for one of the most important field research procedures, the researchers used the experimental method for its suitability to the nature of the research and because this method is characterized by the accuracy of its results. For the academic year ( 2021-2022). The original research community consisted of (106), and the research samples were chosen by the simple random method, which included (20) students, divided into two equal groups with (10) students for each group, after (10) students were excluded due to absence from the initial tests and units. Educational control group: used the method followed by the teacher. Experimental group: used the strategy of schematic shapes. The researchers proceeded to conduct equivalence and after that to choose the skills and appropriate tests for them by taking the opinion of experts and then proceeded to conduct an exploratory experiment and a tribal test. The researchers designed educational units According to the strategy of schematic shapes, the program was implemented for a period of 12 weeks, the time of the educational unit was 45 minutes, and then the post test was conducted and the statistical bag was used to reach results that in turn led to the most important conclusions, including the superiority of the experimental group over the control group in the post test and learning the skill of handling, suppression, scoring and skill performance of some skills The basic football strategy helped the diagrams to increase the students’ self-confidence from By giving them the opportunity to design shapes that indicate the extent of their understanding of the subject in light of the results of the current research, the researcher recommends and most importantly to emphasize the use of the illustrative shapes strategy because of its importance in adding some pleasure and desire to learn to any scientific subject, and this is what the researcher touched during the experiment. Teachers to not be limited to the methods used and the need to diversify the use of methods, and to use the strategy of graphic forms as modern methods that have been proven by multiple studies to be effective in learning.